Gazelles - Dalton, Sheila (Markham, Ont. : Grolier, 1990)
Describes the various kinds of gazelles, their physical and behavioral characteristics, their mating habits, and their future survival.
Includes glossary and index
Keywords: Gazelles -- Juvenile literature